2003
DOI: 10.2105/ajph.93.1.138
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability and the Patient–Practitioner Relationship: The Roles of Gatekeeping and Primary Care Performance

Abstract: Objectives. We examined whether patients’ perceptions of their relationships with primary care practitioners (PCPs) vary by vulnerability status and assessed the extent to which gatekeeping arrangements and primary care performance moderate potential disparities. Methods: We used the nationally representative 1996–1997 Community Tracking Study Household Survey as our data source. Results. Whites reported better patient–practitioner relationships than minorities. Requirements that patients select a PCP and ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 28 publications
0
36
0
2
Order By: Relevance
“…Ngo-Metzger, Legedza, and Phillips (2004) recommended that providers must try to understand and incorporate cultural understanding into their health care practice. These problems were exacerbated in a managed care setting employing gatekeepers in which ethnic minorities were less likely than White patients to receive appropriate care (Cooper et al, 2003;Hargraves, Cunningham, & Hughes, 2001;Shi, Forrest, von Schrader, & Ng, 2003;Van Ryn & Fu, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Ngo-Metzger, Legedza, and Phillips (2004) recommended that providers must try to understand and incorporate cultural understanding into their health care practice. These problems were exacerbated in a managed care setting employing gatekeepers in which ethnic minorities were less likely than White patients to receive appropriate care (Cooper et al, 2003;Hargraves, Cunningham, & Hughes, 2001;Shi, Forrest, von Schrader, & Ng, 2003;Van Ryn & Fu, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…A large study reported that requiring patients to select a primary care provider and obtain referral authorization did not affect racial disparities in the quality of primary care. 9 However, better continuity was associated with reduced disparities, suggesting that encouraging patients to go through their primary care providers before visiting a specialist might be desirable. In short, continuity is the friendly face of gatekeeping.…”
Section: Discussionmentioning
confidence: 99%
“…This became known, mostly pejoratively, as "gatekeeping." The PCPs' function as gatekeepers was perceived by the majority of PCPs as a cause of damaged relationships between doctors and patients, contributing to poorer patient outcomes (Feldman et al, 1998;Hadley et al, 1999;Shi et al, 2003), as well as diminished trust and patient satisfaction (Shi et al, 2003).…”
Section: Primary Care Physicians' Professional Environmentmentioning
confidence: 99%